Taxonomy, phylogeny, and bioactive potential of Xylariales (Sordariomycetes, Ascomycota) from Thailand: novel species discovery, new host and geographical records, and antibacterial properties - Achala R. Rathnayaka; K. W. Thilini Chethana; Areerat Manowong; Amuhenage T. Bhagya; Hsan Win; Zaw L. Tun; Ausana Mapook; Kevin D. Hyde (MycoKeys)
Xylariales (Sordariomycetes, Ascomycota) comprise a wide range of species that exhibit considerable variation in stromatic characteristics, including conspicuous to inconspicuous perithecia and unitunicate asci. Most known species are endophytes and saprobes, recognized for producing secondary metabolites of fundamental importance in the pharmaceutical and chemical industries. The main objectives of this study were to identify novel species, document new host and geographical records within the families Diatrypaceae, Hypoxylaceae, and Xylariaceae in northern and central Thailand, and explore the bioactive properties of secondary metabolites produced by selected Xylariales species. Taxa were identified through morphological examination, supported by phylogenetic analyses using maximum likelihood and Bayesian inference based on LSU, ITS, rpb2, and β-tub gene sequences. These taxa are accompanied by comprehensive descriptions and illustrations. Xylariales cultures were screened for preliminary antibacterial activity against the bacterial pathogens Bacillus subtilis (Gram-positive) and Escherichia coli (Gram-negative). Based on the screening results, two newly introduced species (Annulohypoxylon chiangraiense and Hypoxylon thailandicum) and two known species (Xylaria chrysanthum and Daldinia eschscholtzii), which exhibited antibacterial activity, were selected for secondary metabolite extraction. Crude extracts from these isolates were chemically profiled using high-performance liquid chromatography (HPLC) and Q-TOF analyses, revealing a variety of potential compounds. The present study enhances our understanding of the taxonomic diversity and bioactive potential of Xylariales by introducing five new species, reporting nine new host records—including one new geographical record—and evaluating the bioactive properties of selected Xylariales cultures.